2021
DOI: 10.1177/21582440211052549
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Realized Absorptive Capacity in Colombian Firms: The Mediating Role of the Organizational Climate for Innovation

Abstract: The absorptive capacity is related to knowledge evaluation and acquisition (Potential Capacity), as well as to the transformation and exploitation of such knowledge (Realized Capacity). This research aims to analyze the absorptive capacity in Colombian companies and to investigate whether the Realized capacity can be predicted from the Potential capacity. Likewise, due to the importance of the context on the absorptive capacity development, the mediating role of the organizational climate for innovation was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
4
0
1
Order By: Relevance
“…Thus, Cantwell [ 3 ] remembers that there has been an increasing awareness of the importance of absorptive capacity on the part of firms [ 96 ]. In this same line, Contreras et al [ 97 ] show that companies should have an organizational climate that allows them to acquire and transform knowledge in order to increase their innovativeness and be more competitive in a globalized world. Having this in mind, firms and locations co-evolve with one another, and it is possible to appreciate the rise of knowledge connectivity in innovation systems, that is a new underlying reality of the international business field [ 98 ].…”
Section: Research Resultsmentioning
confidence: 99%
“…Thus, Cantwell [ 3 ] remembers that there has been an increasing awareness of the importance of absorptive capacity on the part of firms [ 96 ]. In this same line, Contreras et al [ 97 ] show that companies should have an organizational climate that allows them to acquire and transform knowledge in order to increase their innovativeness and be more competitive in a globalized world. Having this in mind, firms and locations co-evolve with one another, and it is possible to appreciate the rise of knowledge connectivity in innovation systems, that is a new underlying reality of the international business field [ 98 ].…”
Section: Research Resultsmentioning
confidence: 99%
“…Es decir, organizaciones que cuenten con un liderazgo que fomente un entorno de aprendizaje y clima organizacional colaborativo que permita que los individuos puedan realizar actividades en su nivel óptimo para crear valor y, a su vez, identificar, asimilar, explotar y transformar el conocimiento interno y externo (Contreras et al, 2021;Estivalete & Pedrozo, 2018;Gibb et al, 2017;Mastio et al, 2020).…”
Section: Capacidad De Absorción De Conocimiento (Capab) Y Rendimiento...unclassified
“…atmosphere and innovation performance, and negatively regulates the relationship between negative emotional atmosphere and innovation performance (Havlovic and Keenan, 1995;Contreras et al, 2021). Specifically, employees with a positive organizational climate are likely to find key information or inspiration for innovation with positive emotions, and are more likely to show innovative behaviors, and then promote the improvement of innovation performance (Bu et al, 2021), when faced with challenging stressors (Binnewies and Wrnlein, 2011).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Organizational climate refers to an overall attribute of an organization, which is the enduring characteristic of the organization or environment perceived by the organization or its members ( Forehand and Haller, 1964 ; Schneider and Bartlett, 2010 ). Based on the conservation of resource theory, positive organizational climate is a valuable social resource that has a significant impact on employees’ individual innovation performance ( Contreras et al, 2021 ). On the one hand, research have shown that, team members with positive organizational climate can effectively use social resources to explain and integrate different ideas and views, so they are more focused on creative tasks and less distracted by psychological anxiety, enhance the positive emotional atmosphere ( Bu et al, 2021 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%